Engaging with partners to strengthen nutrition, livelihoods and climate adaptation research: Workshop report from Viqueque Municipality, Timor-Leste - Bonis-Profumo, Gianna; Ximenes, Imanuel; Simões, N.; Pereira, Mario; Mills, David (WorldFish, 2023)
WorldFish operates a transdisciplinary research-in-development program in Timor-Leste, hosted by the national government and the Directorate General of Fisheries, Aquaculture and Marine Resources (DG-FAMR). Two new projects started in Viqueque Municipality in 2022, working to support aquatic foods systems with nutrition-sensitive, inclusive and climate adaptation approaches. A workshop provided a platform to engage and consult with national, municipal and local partners, stakeholders and communities, aiming to strengthen partnerships at the municipality level. This brief provides a summary of the workshop and the outcomes of the consultation, and demonstrates the first steps towards adaptive, sustainable and nutrition-sensitive transformation of aquatic food systems.